1996
DOI: 10.1002/j.1556-6978.1996.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Multicultural Counseling Training at CACREP‐Accredited Counselor Education Programs

Abstract: This article presents an exploratory study to determine the status of multicultural counseling training in counseling programs accredited by the Council for the Accreditation of Counseling and Related Educational Programs (CACREP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…As of 1996, Dinsmore and England (1996) found that the multicultural program design used most frequently by CACREP programs (N = 32, 47%) included a multicultural course requirement and infusion of multicultural content in all courses. However, they also found that few programs focused on multicultural content in courses related to counseling theories (30%), counseling skills (46%), and practica/internships (41%).…”
Section: Multicultural Training Models In Cacrep Programsmentioning
confidence: 98%
“…As of 1996, Dinsmore and England (1996) found that the multicultural program design used most frequently by CACREP programs (N = 32, 47%) included a multicultural course requirement and infusion of multicultural content in all courses. However, they also found that few programs focused on multicultural content in courses related to counseling theories (30%), counseling skills (46%), and practica/internships (41%).…”
Section: Multicultural Training Models In Cacrep Programsmentioning
confidence: 98%
“…Many counselor education programs have already adopted an infusion approach to promoting multicultural competence (Dinsmore & England, 1996). Extending this infusion approach to include more explicit attention to how counselors may be alert to and assess for advocacy needs, integrate advocacy theories into their practice, and develop advocacy skills is needed.…”
Section: Infusing Advocacy Into Counselor Education Programsmentioning
confidence: 99%
“…Over the last 20 years, multicultural counseling advocates have called for more diverse faculty representation in counselor education (Atkinson, 1983;Atkinson, Morton, & Sue, 1989;Young, Charnley, & Withers, 1990), with very little increase in the numbers of senior-level ethnic minority counselor educators. Dinsmore and England (1996), for instance, found that the percentages of counselor educators by ethnic group were significantly different from the percentages for each ethnic group in the U.S. population. They found that 15% of counselor educators were non-White, compared with a 25% non-White percentage in the general population.…”
mentioning
confidence: 95%